Розробка додатку для аналізу мережного трафіку - Чистюк, Д. С. (ХНУРЕ, 2024)
The purpose of the work is to formulate the concept of network traffic analysis, to explore methods of analyzing corporate traffic, working principle of the network traffic analyzer and its advantages. As a result, own traffic analysis application was developed. This application provides real-time visualization of network traffic activity and creation of customized reports in different types of content such as text, graphics, and graphs. These tools will enable many network professionals to create secure, efficient, well designed and performance optimized networks.
Keywords: мережний трафік; аналіз мережного трафіку